THE CHARACTERISTICS OF ACTIVATED CHARCOAL FROM JATROPHA SEED SHELL (Jatropha curcas LINN) AND ITS QUALITY TEST TO GROUND WATER - Alimah, Dewi; Sutapa, J. P. Gentur (LIPI-Press, 2012)
Jatropha seed shell (Jatropha curcas Linn) produced as wastes of jatropha oil manufacturing can be convertedto activated charcoal. The purpose of this experiment was to investigate the characteristic of activatedcharcoal produced from jatropha seed shell and to analyze its quality to ground water. The seed shells werecarbonized into charcoal at 500°C for 3 hour. The charcoal was activated at 800°C and 900°C for 0, 30, 60, and 90min. The results showed that moisture content, volatile matter content, iodine and methylene blue adsorption hadqualify met to the standards of quality activated charcoal powder according to SNI 06-3730-1995. Most of valueof fixed carbon met the qualify standard while ash content did not meet the standards. Based on the adsorptivecapacity of iodine, the charcoal increased the quality of ground water as recommended by the Ministry of Healthof 416/Menkes/Per/IX/1990.